2015
DOI: 10.1038/srep11165
|View full text |Cite
|
Sign up to set email alerts
|

Large and Tunable Polar-Toroidal Coupling in Ferroelectric Composite Nanowires toward Superior Electromechanical Responses

Abstract: The collective dipole behaviors in (BaTiO3)m/(SrTiO3)n composite nanowires are investigated based on the first-principles-derived simulations. It demonstrates that such nanowire systems exhibit intriguing dipole orders, due to the combining effect of the anisotropic electrostatic interaction of the nanowire, the SrTiO3-layer-modified electrostatic interaction and the multiphase ground state of BaTiO3 layer. Particularly, a strong polar-toroidal coupling that is tunable by the SrTiO3-layer thickness, temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 36 publications
2
24
0
Order By: Relevance
“…Recently, it has been revealed that topological dipole states like vortices with a toroidal order [11][12][13] can be stabilized in ferroelectric nanostructures under certain conditions. Interestingly, the toroidal order can coexist with polar order forming polar-toroidal multiorder (PTMO) states 14,15 and even skyrmion-like states 16 in specific ferroelectric nanostructures.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, it has been revealed that topological dipole states like vortices with a toroidal order [11][12][13] can be stabilized in ferroelectric nanostructures under certain conditions. Interestingly, the toroidal order can coexist with polar order forming polar-toroidal multiorder (PTMO) states 14,15 and even skyrmion-like states 16 in specific ferroelectric nanostructures.…”
Section: Introductionmentioning
confidence: 99%
“…25 The second kind of systems are particular nanosystems made of rhombohedral phase ferroelectrics and under anisotropic screening condition, such as BaTiO 3 and BaTiO 3 /SrTiO 3 composite nanowires. [14][15][16]23 The most important feature of a PTMO state is the coexistence and possible coupling between the polar order and toroidal order, which gives rise to the distinguished behaviors of a PTMO state compared with purely toroidal or polar state. For example, as a result of the polar-toroidal coupling, superior piezoelectric and piezotoroidal responses 15 and interesting dynamical characteristics 26 are found in PTMO states.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of ferroelectrics, several theoretical studies [20][21][22][23][24] have proposed complex polarization topologies (reminiscent of rotational spin topologies) in low-dimensional structures. The models have predicted the formation of polarization waves, vortices and so on that can be characterized by an emergent order parameter, a so-called electric toroidal moment (G = (1/2V ) r × P(r) d 3 r; refs 20,22,25).…”
mentioning
confidence: 99%
“…The presence of this axial polarization component is interesting because it suggests the formation of a multi-order-parameter state. In turn, electric-field control of toroidal order is of great interest because it offers the potential for new cross-coupled functions [20][21][22][23][24] . To explore this concept, the time-dependent evolution of both the vortex and a 1 /a 2 regions of a mixed-phase structure was explored under an applied out-of-plane voltage (15 V) using phase-field models.…”
mentioning
confidence: 99%